Focal Brain Therapy: Transcranial Pulse Stimulation with Ultrasound in Alzheimer's Disease—A New Navigated Focal Brain Therapy (Adv. Sci. 3/2020). Issue 3 (5th February 2020) - Beisteiner, Roland; Matt, Eva; Fan, Christina; Baldysiak, Heike; Schönfeld, Marleen; Philippi Novak, Tabea; Amini, Ahmad; Aslan, Tuna; Reinecke, Raphael; Lehrner, Johann; Weber, Alexandra; Reime, Ulrike; et al.
Abstract : In article number 1902583, Roland Beisteiner and co‐workers describe a brain activation technique for treatment of Alzheimer's disease. Transcranial pulse stimulation (TPS) applies ultrashort ultrasound pulses to activate neuronal resources. A therapeutic breakthrough is secure clinical targeting and access to deep brain areas. After 2 weeks of treatment, memory performance improves for up to 3 months.